(untitled) (Ustozlar uchun, 2025)
Parallel corpora—large collections of texts and their translations aligned at sentence or paragraph level—have become one of the most influential resources in contemporary Translation Studies. They serve as a foundation for empirical linguistic research, translator training, contrastive analysis, and the development of machine translation and other NLP technologies. This article provides an expanded theoretical and analytical overview of parallel corpora, explaining their structure, functions, and practical applications. Drawing on examples from widely used corpora such as Open Subtitles, the UN Corpus, the Bible Corpus, and multilingual literary collections, the study illustrates how parallel corpora allow researchers to identify translation strategies, examine equivalence relations, and detect cross-linguistic tendencies. The article argues that parallel corpora have reshaped the discipline by enabling data-driven methodologies that complement and extend traditional translation theories. The implications for translation pedagogy, professional practice, and computational linguistics are discussed, emphasizing the central role of corpus-based evidence in modern research.